TEACHERS’ PERCEPTION ON THE USE OF WORDWALL MEDIA IN TEACHING ENGLISH BASIC VOCABULARY - Sya'diyah, Halimatu; Novi Rahmania Aquariza; Mujad Didien Afandi; Nailul Authar (Universitas Islam Lamongan, 2024)
This study focuses on describing teachers' perceptions and problems faced in using Wordwall media in teaching English basic vocabulary. This research is descriptive with a qualitative approach. The data in this study are teachers' perceptions and problems faced with the use of Wordwall media in teaching English basic vocabulary. The source of the data is teachers who teach at the junior secondary school level. The data were collected by using questionnaires. The data obtained from the questionnaire were then created a table, analyzed, and interpreted. This study found teachers' positive perceptions towards the use of Wordwall as a medium for learning English basic vocabulary and the problems faced by teachers when using Wordwall. The study concluded that teachers were satisfied with the Wordwall learning media to be used in teaching English basic vocabulary.